Pseudohypoaldosteronism in a newborn male with functional polymorphisms in the mineralocorticoid receptor genes - Hyun Ah Jeong; Yoon Kyoung Park; Yeong Sang Jung; Myung-Hyun Nam; Hyo-Kyoung Nam; Kee Hyoung Lee; Young-Jun Rhie (Korean Society of Pediatric Endocrinology, 2015)
Hyponatremia and hyperkalemia in infancy can be attributed to various causes, originating from a variety of renal and genetic disorders. Pseudohypoaldosteronism type 1 (PHA1) is one of these disorders, causing mineralocorticoid resistance that results in urinary salt wasting, failure to thrive, metabolic acidosis, and dehydration. PHA1 is heterogeneous in etiology. Inactivating mutations in the NR3C2 gene (4q31.1), which encodes the mineralocorticoid receptor, causes a less severe autosomal dominant form that is restricted to the kidney, while mutations in the amiloride-sensitive epithelial sodium channel gene (alpha subunit=SCNN1A, 12p13; beta subunit=SCNN1b, 16p12.2-p12.1; gamma subunit=SCNN1G, 16p12) causes a more severe autosomal recessive form, which has systemic effects. Here we report a neonatal case of kidney restricted PHA1 (renal type of PHA1) who first showed laboratory abnormalities before obvious PHA1 manifestations, with two functional polymorphisms in the NR3C2 gene. This is the second genetically confirmed case in Korea and the first to show functional polymorphisms that have previously been reported in the literature.